Teachers’ creativity-fostering behaviours and emotional intelligence as predictors of students’ performance in circle geometry - Chukwuemeka Metu; Chika Ugwuanyi (Revista de Estudios e Investigación en Psicología y Educación)
This research examines how teachers‘ creativity-fostering behaviours and emotional intelligence can predict their students’ performance in circular geometry. The study was guided by two research questions and two hypotheses, and the research methodology employed was that of a survey. The starting population consisted of a total of 2056 people, and a multi-stage sampling procedure was used to draw a sample of 384 respondents, female and male: 336 students aged 15-19 and 48 teachers aged 35-58. The Teacher Creativity Fostering Scale (TCFBS), the Teacher Emotional Intelligence Scale (TEIS) and the Circular Geometry Performance Test (CGPT) were used to obtain the research data. For the statistical analysis of the data, correlations and analysis of variance were carried out. Teacher creativity-enhancing behaviours were found to predict 58% of student performance in circular geometry, while teachers' emotional intelligence explained 41%. These findings highlight the importance of fostering creative problem-solving strategies and designing tasks tailored to students' individual strengths.